Late Miocene Onset of Tasman Leakage and Southern Hemisphere Supergyre Ushers in Near‐Modern Circulation. Issue 18 (14th September 2021) - Christensen, Beth A.; De Vleeschouwer, David; Henderiks, Jorijntje; Groeneveld, Jeroen; Auer, Gerald; Drury, Anna Joy; Karatsolis, Boris Theofanis; Lyu, Jing; Betzler, Christian; Eberli, Gregor P.; Kroon, Dick
Abstract: This study provides a Miocene‐to‐recent history of Tasman Leakage (TL), driving surface‐to‐intermediate waters from the Pacific into the Indian Ocean. TL, in addition to Indonesian ThroughFlow (ITF), constitutes an important part of the Southern Hemisphere Supergyre. Here, we employ deep‐sea benthic δ 13 C timeseries from the southwestern Pacific and eastern Indian Oceans to identify the history of Tasman Leakage. The δ 13 C results combined with sedimentary evidence show that an inter‐ocean connection south of Australia existed from 7 Ma onward. A southward shift in Westerlies combined with a northward movement of Australia created the oceanic corridor necessary for Tasman Leakage (between Australia and the sub‐Antarctic Front) at this time. Furthermore, changes in the northern limb of the Supergyre (ITF) are evident in the sedimentary record on Broken Ridge from ∼3 to 2 Ma when Banda Sea intermediate waters started originating from the North Pacific. Plain Language Summary: Global ocean circulation allows for the distribution of heat between different latitudes and different water depths. It has long been understood that much of the return flow from the Pacific to the Atlantic occurs through the Indonesian Throughflow, but more recently, oceanographers have identified another, deeper pathway south of Australia: the Tasman Leakage. This connection consists of Pacific waters that leave the Tasman Sea by flowing southwest around Australia, into the Indian Ocean and ultimately back into the Atlantic. We use carbon isotopes of benthic foraminifera, coupled with sedimentation patterns around Australia and the Indian Ocean, to determine the onset of this new pathway in global thermohaline circulation: This occurred around 7 Ma. This onset was coincident with major global climatic and oceanographic change and was controlled by the position of the Australian continent and the sub‐Antarctic Front. TL onset was only able to occur when Australia had moved far enough north to allow for westward flow. Key Points: Benthic δ 13 C time‐series from the southwestern Pacific and eastern Indian Ocean suggest onset of Tasman Leakage at 7 Ma Latitudinal movement of the Australian continent away from the sub‐Antarctic Front creates the oceanic corridor necessary for Tasman Leakage The Late Miocene onset of Tasman Leakage completed the Southern Hemisphere Supergyre and ushered in the near‐modern ocean circulation style